ARSENIC LEVEL IN FOOD AT SIX COMMUNES OF VU THU DISTRICT, THAI BINH PROVINCE IN 2017 (Vietnam Journal of Community Medicine, 2022)
Objectives: Identify arsenic level in food in 6 communes of Vu Thu district, Thai Binh province in 2017.Method: This is a cross-sectional study.Result: The study showed that the proportion of fish samples in dry season was higher than that in rainy season, the bottom aquifer was higher than the surface water and stagnant pond had higher rate of arsenic level than circulation pond. 100% of mussel and 95% of shellfish had the arsenic level exceeding the permitted standards (1mg/kg). Only 8,3% of terrestrial vegetable samples and 5% of aquatic vegetable samples had arsenic level exceeding the permitted limit (1mg/kg).Conclusion: The food samples at six communes of Vu Thu district, Thai Binh province had arsenic level exceeding the permitted limit, especially fish at the bottom of pond and shellfish.
Keywords: Arsenic level, in food, fish at the bottom.